Multiple sample data acquisition system for low resistivity measurement using four point probe technique / Fazlina Ahmat Ruslan - Ahmat Ruslan, Fazlina (2001)
This project presented a data acquisition system for simultaneous multiple sample resistance measurements using four point probe technique [1] [2], The system uses the PCLD785B relay board controlled by parallel input-output 8255A PIA emulation through a PCL724B card to perform multiple sample measurements by signal switching. The system, which is controlled by a PC, is able to log and store temperature and resistivity measurements. Voltage versus temperature measurements for two ceramic samples were performed and compared.